2021
DOI: 10.3390/diagnostics11040637
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visual Information and Sex on Postural Control in Children Aged 6–12 Years Assessed with Accelerometric Technology

Abstract: The performance of postural control is believed to be linked to how children use available sensory stimuli to produce adequate muscular activation. Therefore, the aim of the present study was to thoroughly explore postural stability under normal conditions and without visual information in postural control in children aged 6–12 years during static single-leg support. A descriptive cross-sectional study was conducted with 316 children (girls = 158). The analyzed variables were the mean and maximum values obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
5
3
0
Order By: Relevance
“…Boys outperformed girls in all physical fitness tests with the exception of the one-legged stance test, where girls outperformed boys. The better static balance of girls is in line with results from previous research reporting gender differences in the development of postural control [ 74 77 ]. Better static balance of girls in the ninth year of life might be related to a faster maturation of the vestibular system [ 78 , 79 ] and a faster development of sensory integration ability [ 79 , 80 ] in girls.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Boys outperformed girls in all physical fitness tests with the exception of the one-legged stance test, where girls outperformed boys. The better static balance of girls is in line with results from previous research reporting gender differences in the development of postural control [ 74 77 ]. Better static balance of girls in the ninth year of life might be related to a faster maturation of the vestibular system [ 78 , 79 ] and a faster development of sensory integration ability [ 79 , 80 ] in girls.…”
Section: Discussionsupporting
confidence: 90%
“…Better static balance of girls in the ninth year of life might be related to a faster maturation of the vestibular system [ 78 , 79 ] and a faster development of sensory integration ability [ 79 , 80 ] in girls. Previous research reported a higher reliance on visual information for postural control in preadolescent boys compared to girls [ 74 ], and our results may thus indicate a better sensory reweighting ability in girls compared to boys in the ninth year of life.…”
Section: Discussionsupporting
confidence: 54%
“…Boys outperformed girls in all physical fitness tests with the exception of the one-legged stance test, where girls outperformed boys. The better static balance of girls is in line with the results of previous research [81][82][83][84] and might be related to a faster maturation of the vestibular system [85,86] and a faster development of sensory integration ability [86,87] in girls. Previous research has shown a higher reliance on visual information for postural control in preadolescent boys compared to girls [81], and our results may thus indicate a better sensory reweighting ability in girls compared to boys in the ninth year of life.…”
Section: Source Of Variancesupporting
confidence: 89%
“…The first four physical fitness tests thus clearly represent the latent construct physical fitness. The low correlation between the one-legged stance with the other tests may be explained by the fact that performance in a static balance test is not energetically-driven, but, as mentioned above, reflects differences in sensory integration and reweighting abilities [81,86,88]. This result is in line with previous research reporting no association of balance and muscular strength [89][90][91].…”
Section: Source Of Variancesupporting
confidence: 86%
“…Many studies have convincingly demonstrated the effect of the “age” factor on the relationship between psychophysiological and stabilometric characteristics of postural control [ 25 , 66 , 67 , 119 ]. It has been shown that the variability of COP oscillations decreases with the maturation of children up to 10–12 years [ 120 ] and increases with aging after 40 years [ 119 ]. Numerous studies have demonstrated that postural control parameters in older adults are reduced and, accordingly, the risk of falling considerably increases [ 25 , 30 , 66 , 67 , 119 ].…”
Section: Psychophysiological Mechanisms and Factors Determining The I...mentioning
confidence: 99%